A CONCEPTUAL STUDY ON THE IMPLICATIONS OF FINANCIAL LITERACY RATE ON THE COMPANY PROFITABILITY OF MSMEs - Nicholas King King Herijanto; Raden Aswin Rahadi (International Journal of Accounting, Finance and Business, 2020)
Due to its significant contribution and potential for the national economy as a whole, micro, small and medium enterprises (MSMEs) are currently perceived as the key to the creation of new economic sources and drivers in Indonesia. However, despite the potential, in reality, there are still several fundamental problems faced by the majority of MSMEs in Indonesia. These problems are identified to be caused by the low levels of financial literacy among Indonesian, especially the entrepreneur groups. The low level of financial literacy has a great potential to disrupt the MSMEs growth and performance, especially in profitability, which ultimately lead to the unfavorable economic conditions in Indonesia. The purpose of this paper is to find the relationship between financial literacy and MSMEs profitability, and what factors determine both variables. The data in this study is collected from existing literature such as journals, books, and research publications that are relevant to the research topics. Based on the literature review, the research was eventually able to generate a simple conceptual framework on the relationship between financial literacy rate and MSMEs profitability. The framework suggested that the demographic and socio-economic characteristics as well as financial education will directly affect the MSMEs financial literacy rate, while as moderating factors, characteristics of a business will indirectly influence the MSMEs profitability.